New formalism for self-consistent parameters optimization of highly efficient solar cells - Sachenko, A.V.; Kostylyov, V.P.; Kulish, M.R.; Sokolovsky, L.O.; Shkrebtii, A.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
We analyzed self-consistently photoconversion efficiency of direct-gap A³B⁵ semiconductors based solar cells and optimized their main physical characteristics. Using gallium arsenide (GaAs) as an example and new efficient optimization formalism, we demonstrated that commonly accepted light re-emission and reabsorption in solar cells in technologically produced GaAs (in particular, with solid- or liquid-phase epitaxy) are not the main factors responsible for high photoconversion efficiency. As we proved instead, the doping level of the base material and its doping type as well as Shockley-Read-Hall and surface recombination velocities are much more important factors responsible for this photoconversion. We found that the maximum photoconversion efficiency (about 27% for AM1.5 conditions) in GaAs with typical parameters of recombination centers can be reached for p-type base doped at 2∙10¹⁷ cm⁻³. The open-circuit voltage VOC formation features are analyzed. The optimization provides a significant increase in VOC and the limiting photoconversion efficiency close to 30%. The approach of this research allows to predict the expected solar cell (for both direct- and indirect-gap semiconductor) characteristics, if material parameters are known. The applied formalism allows to analyze and to optimize mass production of both tandem solar cell and one-junction SC parameters.